A fluorescent turn-on probe for visualizing lysosomes in hypoxic tumor cells. Issue 10 (3rd May 2016) - Luo, Sihang; Liu, Yingchao; Wang, Feiyi; Fei, Qiang; Shi, Ben; An, Jiancai; Zhao, Chunchang; Tung, Chen-Ho
Abstract : A fluorescent probe localized in lysosomes after reductive cleavage with azoreductase gave strong fluorescence, providing specificity for imaging lysosomes in hypoxic cancer cells. Abstract : A fluorescent probe for fulfilling a lysosome targeting function in hypoxic tumor cells is reported, wherein azoreductase triggers a dramatic fluorescence enhancement and specific imaging of lysosomes in hypoxic cancer cells.